A new species of Choristoneura Lederer, with a key to the species from China (Lepidoptera: Tortricidae: Tortricinae) - Wang, Xin-Pu; Yang, Gui-Jun (Zootaxa, 2008)
Choristoneura was proposed by Lederer (1859), with Tortrix diversana Hübner as its type species. Razowski (1992) provided a contemporary synopsis of the genus from a global perspective, including 41 species. Brown (2005) included 38 species in the genus, with 20 described from the Palearctic Region, 17 from the Nearctic Region, and one from the Afrotropical Region. The larvae of some species of Choristoneura are important forest pests. In North America, C. fumiferana (Clemens), the spruce bud worm, feeds on Picea glauca (Moench) Voss and numerous other Pinaceae (e.g., Prentice, 1966; Thomas, 1987; Lawrence et al., 1997; Trier and Mattson, 1997; Retnakaran et al. 1999). In Europe, C. murinana is a pest of Abies alba Miller (e.g., Merle et al., 1992). And in northwestern China, C. diversana (Hübner) attacks Picea crassifolia Kom. (Hao et al., 2002).